A waterproof paint for a wall protection plate and a method for preparing the same

CN122917604APending Publication Date: 2026-10-16CHONGQING HENGCHUANG FURNITURE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611222517.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]但目前市面上常规护墙板配套涂装多采用传统单层防水涂料,存在明显的性能短板,难以适配护墙板的长效防护需求,传统单层涂料成膜结构单一,涂层致密性差、防水防渗层级不足,防水防潮性能薄弱,水汽、潮气极易透过涂层微观孔隙渗透至护墙板基材及墙体基层,长期处于厨卫、阳台、潮湿地下室、临江沿海潮湿户型等高湿复杂场景时,涂层易出现渗水、返潮、透湿等问题,无法从根源阻断水分侵蚀,导致护墙板基材受潮发霉、发胀变形、腐朽脱落

Benefits of technology

[0012] The beneficial effects of this invention are as follows: This invention adopts a primer and topcoat matching structure; the pore-coupled composite filler in the primer can seal the pores and build a dense waterproof barrier layer; the modified titanium dioxide in the topcoat enhances the ultraviolet shielding ability; at the same time, the cross-linking of polycarbodiimide and acrylic emulsion further improves the density of the paint film; it has outstanding water resistance and is not prone to bubbling and whitening after long-term immersion in water; it has excellent resistance to artificial weathering and aging, with low gloss loss and peeling after exposure to light, and small hardness reduction; the primer and topcoat have good compatibility and strong interlayer adhesion, solving the defects of traditional single-layer coatings such as weak waterproofing, easy water seepage, and incomplete seepage prevention, greatly improving the overall waterproof and moisture-proof ability of the wall panel, and can be adapted to complex usage scenarios such as damp indoor spaces, kitchens, bathrooms, and balconies for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The present application relates to a kind of wall protection plate waterproof paint and preparation method thereof, belong to wall protection plate technical field, and wall protection plate waterproof paint is obtained after being sprayed by primer and finish paint superposition;The primer is composed of the following mass parts of raw materials:styrene-acrylic emulsion 38-48 parts, polycarbodiimide crosslinking agent 1.2-2.5 parts, dodecanol ester 1.8-2.8 parts, butanediol isopropyl ether 1-2 parts, polyacrylic acid ammonium salt wet dispersing agent 0.3-0.8 parts, defoaming agent 0.2-0.5 parts, composite filler 9-16 parts, deionized water 26-36 parts.Primer, finish paint matching structure is used;Pore coupling composite filler in primer can block pore, construct dense waterproof barrier;Finish paint modified titanium dioxide improves ultraviolet shielding capacity;Crosslinking of polycarbodiimide and acrylic emulsion is simultaneously utilized, and the dense degree of paint film is further improved;Water resistance is outstanding, and it is not easy to bubble and white for long time immersion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wall panel technology, specifically relating to a waterproof paint for wall panels and its preparation method. Background Technology

[0002] As a new type of wall decoration and protection material, wall panels have excellent constant temperature insulation and sound absorption and noise reduction performance. They can effectively regulate the local indoor temperature, weaken environmental noise, and improve the comfort of living and using the space. At the same time, wall panels have excellent wall protection and decorative beautification effects. They can fully cover and protect the original wall surface of the building, avoid damage to the wall caused by external impacts and friction, and perfectly cover up problems such as unevenness, cracks and defects in the wall base.

[0003] However, most conventional wall panel coatings on the market currently use traditional single-layer waterproof coatings, which have obvious performance shortcomings and are difficult to meet the long-term protection requirements of wall panels. Traditional single-layer coatings have a simple film structure, poor coating density, insufficient waterproof and seepage prevention layers, and weak waterproof and moisture-proof performance. Water vapor and moisture can easily penetrate through the micro-pores of the coating to the wall panel substrate and the wall base. When in high-humidity and complex scenarios such as kitchens, bathrooms, balconies, damp basements, and damp houses near rivers and coasts for a long time, the coating is prone to problems such as water seepage, dampness, and moisture permeation. It cannot stop water erosion from the root, causing the wall panel substrate to become damp, moldy, swollen, deformed, rotten, and fall off. Summary of the Invention

[0004] The purpose of this invention is to provide a waterproof paint for wall panels and its preparation method in order to solve the above-mentioned problems.

[0005] The present invention achieves the above objectives through the following technical solutions: This invention provides a waterproof paint for wall panels, which is obtained by spraying a primer and a topcoat in layers; The primer is composed of the following raw materials in parts by weight: 38-48 parts styrene-acrylic emulsion, 1.2-2.5 parts polycarbodiimide crosslinking agent, 1.8-2.8 parts dodecyl alcohol ester, 1-2 parts butanediol isooctyl ether, 0.3-0.8 parts ammonium polyacrylate wetting and dispersing agent, 0.2-0.5 parts defoamer, 9-16 parts composite filler, and 26-36 parts deionized water; The topcoat is composed of the following raw materials in parts by weight: 42-52 parts pure acrylic emulsion, 1.2-2.5 parts polycarbodiimide crosslinking agent, 2-3 parts dodecyl alcohol ester, 1-2 parts butylene glycol isooctyl ether, 0.3-0.8 parts ammonium polyacrylate wetting and dispersing agent, 0.2-0.4 parts defoamer, 7-13 parts modified titanium dioxide, and 24-34 parts deionized water.

[0006] As a further optimization of the present invention, the modification process of the modified titanium dioxide is as follows: (a) Pretreatment activation: Titanium dioxide is immersed in 0.5-1.0 mol / L phosphoric acid solution with a solid-liquid ratio of 1:5-1:10 and activated at 80-100℃ for 2-4 h. After washing and drying, phosphoric acid activated titanium dioxide is obtained. (ii) Solvent dispersion modification: Add DL-411 aluminate to anhydrous ethanol to prepare a 2-5% mass fraction coupling agent dilute solution, stir evenly to obtain the modified solution; (III) Powder coating: Add phosphoric acid activated titanium dioxide to the modified liquid, control the solid-liquid ratio at 1:4-1:8, and stir at 350-400 rpm for 30-60 min; (iv) Heating and curing: After stirring, heat to 110-130℃ and keep warm for 1.5-3 hours; (v) Crushing and sieving: After cooling, the agglomerated powder is broken up and passed through a 200-300 mesh sieve to remove large agglomerated particles. The sieve-under material is collected to obtain modified titanium dioxide.

[0007] As a further optimization of the present invention, the composite packing is composed of a guest packing and a host material coupled through pores; the volume ratio of the guest packing to the host material is 0.35:1.

[0008] As a further optimization of the present invention, the preparation process of the composite filler is as follows: the guest filler and the host material are mixed and ultrasonically vibrated for 20-40 minutes to couple the pores and form a composite filler.

[0009] As a further optimization of the present invention, the guest filler is selected from nano-calcium carbonate and nano-rutile. One or more of the following, wherein the nano-calcium carbonate has a particle size of 40-60 nm, and nano-rutile... The particle size is 25-40 nm.

[0010] As a further optimization of the present invention, the host material is selected as cenospheres; the particle size of the cenospheres is 30-50μm, and the shell wall pores are 200nm-600nm.

[0011] This invention also provides a method for preparing a waterproof paint for wall panels, comprising the following steps: Primer preparation: S1, at 25℃, add deionized water to the stirred tank and stir at 300-500 rpm. Then add dodecyl alcohol ester and butanediol isooctyl ether in sequence and stir for 3-5 min. Adjust the pH of the system to 7.5-9.0 using a pH adjuster. S2, add ammonium polyacrylate wetting and dispersing agent and composite filler to the stirred tank, and disperse at 1200-1500 rpm for 20-30 min; S3, adjust the speed to 400-600 rpm and add styrene-acrylic emulsion to the mixing tank, stir for 10-15 minutes, then add defoamer and stir for 5-10 minutes; S4, system temperature controlled at 30-35℃, add polycarbodiimide crosslinking agent to the stirred tank and stir for 15-20 minutes; S5, filtered through an 80-120 mesh filter, yields the primer; Topcoat preparation: S1, at room temperature, add deionized water to the stirred tank and stir at 300-500 rpm. Then add dodecyl alcohol ester and butanediol isooctyl ether in sequence and stir for 3-5 minutes. Adjust the pH of the system to 7.5-9.0 using a pH adjuster. S2, add ammonium polyacrylate wetting and dispersing agent and modified titanium dioxide into the stirred tank, and disperse at high speed of 1200-1500 rpm for 20-30 min; S3, adjust the speed to 400-600 rpm and add pure acrylic emulsion to the mixing tank, stir for 10-15 minutes, then add defoamer and stir for 5-10 minutes; S4, system temperature controlled at 25-30℃, add polycarbodiimide crosslinking agent to the stirred tank and stir for 15-20 min; S5, after being filtered through a 100-120 mesh filter, yields the topcoat.

[0012] The beneficial effects of this invention are as follows: This invention adopts a primer and topcoat matching structure; the pore-coupled composite filler in the primer can seal the pores and build a dense waterproof barrier layer; the modified titanium dioxide in the topcoat enhances the ultraviolet shielding ability; at the same time, the cross-linking of polycarbodiimide and acrylic emulsion further improves the density of the paint film; it has outstanding water resistance and is not prone to bubbling and whitening after long-term immersion in water; it has excellent resistance to artificial weathering and aging, with low gloss loss and peeling after exposure to light, and small hardness reduction; the primer and topcoat have good compatibility and strong interlayer adhesion, solving the defects of traditional single-layer coatings such as weak waterproofing, easy water seepage, and incomplete seepage prevention, greatly improving the overall waterproof and moisture-proof ability of the wall panel, and can be adapted to complex usage scenarios such as damp indoor spaces, kitchens, bathrooms, and balconies for a long time. Detailed Implementation

[0013] The present application will now be described in further detail. It should be noted that the following specific embodiments are only used to further illustrate the present application and should not be construed as limiting the scope of protection of the present application. Those skilled in the art can make some non-essential improvements and adjustments to the present application based on the above application content.

[0014] Unless otherwise specified, all methods used in this invention are conventional methods known to those skilled in the art, and all reagents and materials used are commercially available products unless otherwise specified.

[0015] The defoamer used in this invention is BYK-038; In this invention, the polycarbodiimide crosslinking agent is selected from Stahl's XL-702; In this invention, the pH adjuster used is AMP-95, which is diluted with 5 times pure water before use.

[0016] Example 1 The modification process of modified titanium dioxide is as follows: (a) Pretreatment activation: Titanium dioxide was immersed in 0.5 mol / L phosphoric acid solution with a solid-liquid ratio of 1:5 and activated at 80℃ for 2 h. After washing and drying, phosphoric acid activated titanium dioxide was obtained. (ii) Solvent dispersion modification: Add DL-411 aluminate to anhydrous ethanol to prepare a 2% (w / w) dilute coupling agent solution, stir evenly to obtain the modified solution; (III) Powder coating: Add phosphoric acid activated titanium dioxide to the modified liquid, control the solid-liquid ratio at 1:4, and stir at 350 rpm for 30 min; (iv) Heating and curing: After stirring, heat to 110℃ and keep warm for 1.5 hours; (v) Crushing and sieving: After cooling, the agglomerated powder is broken up and passed through a 200-mesh sieve to remove large agglomerated particles. The sieve-under material is collected to obtain modified titanium dioxide. The preparation process of the composite filler is as follows: nano-calcium carbonate (particle size of 40nm) and cenospheres are mixed (the volume ratio of guest filler to cenospheres is 0.35:1; the particle size of cenospheres is 30μm, and the shell wall pores are 200nm), and ultrasonic vibration is performed for 20min to couple the pores and form the composite filler. Primer preparation: S1, at 25℃, add 26 parts of deionized water to the stirred tank, stir at 300 rpm, then add 1.8 parts of dodecyl alcohol ester and 1 part of butanediol isooctyl ether in sequence, stir for 3 min, and adjust the pH of the system to 7.5 using a pH adjuster. S2, add 0.3 parts of ammonium polyacrylate wetting and dispersing agent and 9 parts of composite filler to the stirred tank, and disperse at 1200 rpm for 20 min; S3, adjust the speed to 400 rpm and add 38 parts of styrene-acrylic emulsion to the mixing tank, stir for 10 min, then add 0.2 parts of defoamer and stir for 5 min; S4, with the system temperature controlled at 30℃, add 1.2 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 15 minutes; S5, filtered through an 80-mesh filter, yields the primer; Topcoat preparation: S1, at room temperature, add 24 parts of deionized water to the stirred tank, stir at 300 rpm, then add 2 parts of dodecyl alcohol ester and 1 part of butanediol isooctyl ether in sequence, stir for 3 min, and adjust the pH of the system to 7.5 using a pH adjuster. S2, add 0.3 parts of ammonium polyacrylate wetting and dispersing agent and 7 parts of modified titanium dioxide to the stirred tank, and disperse at high speed of 1200 rpm for 20 min; S3, adjust the speed to 400 rpm and add 42 parts of pure acrylic emulsion to the mixing tank, stir for 10 min, then add 0.2 parts of defoamer and stir for 5 min; S4, with the system temperature controlled at 25℃, add 1.2 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 15 minutes; S5, filtered through a 100-mesh filter, yields the topcoat.

[0017] Example 2 The modification process of modified titanium dioxide is as follows: (a) Pretreatment activation: Titanium dioxide was immersed in 0.8 mol / L phosphoric acid solution with a solid-liquid ratio of 1:8 and activated at 90℃ for 3 h. After washing and drying, phosphoric acid activated titanium dioxide was obtained. (ii) Solvent dispersion modification: Add DL-411 aluminate to anhydrous ethanol to prepare a 3% (w / w) dilute coupling agent solution, stir evenly to obtain the modified solution; (III) Powder coating: Add phosphoric acid activated titanium dioxide to the modified liquid, control the solid-liquid ratio at 1:6, and stir at 375 rpm for 45 min; (iv) Heating and curing: After stirring, heat to 120℃ and keep warm for 2.5 hours; (v) Crushing and sieving: After cooling, the agglomerated powder is broken up and passed through a 250-mesh sieve to remove large agglomerated particles. The sieve-under material is collected to obtain modified titanium dioxide. The preparation process of the composite filler is as follows: nano-calcium carbonate (particle size of 50nm) and cenospheres are mixed (the volume ratio of guest filler to cenospheres is 0.35:1; the particle size of cenospheres is 40μm and the shell wall pore size is 450nm), and ultrasonic vibration is performed for 30min to couple the pores and form a composite filler. Primer preparation: S1, at 25℃, add 32 parts of deionized water to the stirred tank, stir at 400 rpm, then add 2 parts of dodecyl alcohol ester and 2 parts of butanediol isooctyl ether in sequence, stir for 4 min, and adjust the pH of the system to 8.0 using a pH adjuster. S2, add 0.5 parts of ammonium polyacrylate wetting and dispersing agent and 12 parts of composite filler to the stirred tank, and disperse at 1350 rpm for 25 min; S3, adjust the speed to 500 rpm and add 42 parts of styrene-acrylic emulsion to the mixing tank, stir for 12 min, then add 0.3 parts of defoamer and stir for 8 min; S4, system temperature controlled at 32℃, add 2 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 18 min; S5, filtered through a 100-mesh filter, yields the primer; Topcoat preparation: S1, at room temperature, add 28 parts of deionized water to the stirred tank, stir at 400 pm, add 2 parts of dodecyl alcohol ester and 1 part of butanediol isooctyl ether in sequence, stir for 4 min, and adjust the pH of the system to 8.0 using a pH adjuster. S2, add 0.5 parts of ammonium polyacrylate wetting and dispersing agent and 10 parts of modified titanium dioxide to the stirred tank, and disperse at high speed of 1350 rpm for 25 min; S3, adjust the speed to 500 rpm and add 48 parts of pure acrylic emulsion to the mixing tank, stir for 12 min, then add 0.3 parts of defoamer and stir for 8 min; S4, system temperature controlled at 28℃, add 1.8 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 17 min; S5, after being filtered through a 110-mesh filter, yields the topcoat.

[0018] Example 3 The modification process of modified titanium dioxide is as follows: (a) Pretreatment activation: Titanium dioxide was immersed in 1.0 mol / L phosphoric acid solution with a solid-liquid ratio of 1:10 and activated at 100℃ for 4 h. After washing and drying, phosphoric acid activated titanium dioxide was obtained. (ii) Solvent dispersion modification: Add DL-411 aluminate to anhydrous ethanol to prepare a 5% (w / w) dilute coupling agent solution, stir evenly to obtain the modified solution; (III) Powder coating: Add phosphoric acid activated titanium dioxide to the modified liquid, control the solid-liquid ratio at 1:8, and stir at 400 rpm for 60 min; (iv) Heating and curing: After stirring, heat to 130℃ and keep warm for 3 hours; (v) Crushing and sieving: After cooling, the agglomerated powder is broken up and passed through a 300-mesh sieve to remove large agglomerated particles. The sieve-under material is collected to obtain modified titanium dioxide. The preparation process of the composite filler is as follows: nano-calcium carbonate (particle size of 60nm) and cenospheres are mixed (the volume ratio of guest filler to cenospheres is 0.35:1; the particle size of cenospheres is 50μm and the shell wall pores are 600nm), and ultrasonic vibration is performed for 40min to couple the pores and form the composite filler. Primer preparation: S1, at 25℃, add 36 parts of deionized water to the stirred tank, stir at 500 rpm, then add 2.8 parts of dodecyl alcohol ester and 2 parts of butanediol isooctyl ether in sequence, stir for 5 min, and adjust the pH of the system to 9.0 using a pH adjuster. S2, add 0.8 parts of ammonium polyacrylate wetting and dispersing agent and 16 parts of composite filler to the stirred tank, and disperse at 1500 rpm for 30 min; S3, adjust the speed to 600 rpm and add 48 parts of styrene-acrylic emulsion to the mixing tank, stir for 15 min, then add 0.5 parts of defoamer and stir for 10 min; S4, system temperature controlled at 35℃, add 2.5 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 20 min; S5, filtered through a 120-mesh filter, yields the primer; Topcoat preparation: S1, at room temperature, add 34 parts of deionized water to the stirred tank, stir at 500 rpm, add 3 parts of dodecyl alcohol ester and 2 parts of butanediol isooctyl ether in sequence, stir for 5 min, and adjust the pH of the system to 9.0 using a pH adjuster. S2, add 0.8 parts of ammonium polyacrylate wetting and dispersing agent and 13 parts of modified titanium dioxide to the stirred tank, and disperse at high speed of 1500 rpm for 30 min; S3, adjust the speed to 600 rpm and add 52 parts of pure acrylic emulsion to the mixing tank, stir for 15 min, then add 0.4 parts of defoamer and stir for 10 min; S4, system temperature controlled at 30℃, add 2.5 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 20 min; S5, filtered through a 120-mesh filter, yields the topcoat.

[0019] Example 4 The modification process of modified titanium dioxide is as follows: (a) Pretreatment activation: Titanium dioxide was immersed in 0.8 mol / L phosphoric acid solution with a solid-liquid ratio of 1:8 and activated at 90℃ for 3 h. After washing and drying, phosphoric acid activated titanium dioxide was obtained. (ii) Solvent dispersion modification: Add DL-411 aluminate to anhydrous ethanol to prepare a 3% (w / w) dilute coupling agent solution, stir evenly to obtain the modified solution; (III) Powder coating: Add phosphoric acid activated titanium dioxide to the modified liquid, control the solid-liquid ratio at 1:6, and stir at 375 rpm for 45 min; (iv) Heating and curing: After stirring, heat to 120℃ and keep warm for 2.5 hours; (v) Crushing and sieving: After cooling, the agglomerated powder is broken up and passed through a 250-mesh sieve to remove large agglomerated particles. The sieve-under material is collected to obtain modified titanium dioxide. The preparation process of the composite filler is as follows: nano-rutile... (Particle size of 30nm) and cenospheres are mixed (the volume ratio of guest filler and cenospheres is 0.35:1; the particle size of cenospheres is 40μm, and the shell wall pores are 450nm), and ultrasonic vibration is performed for 30 minutes to couple the pores and form a composite filler. Primer preparation: S1, at 25℃, add 32 parts of deionized water to the stirred tank, stir at 400 rpm, then add 2 parts of dodecyl alcohol ester and 2 parts of butanediol isooctyl ether in sequence, stir for 4 min, and adjust the pH of the system to 8.0 using a pH adjuster. S2, add 0.5 parts of ammonium polyacrylate wetting and dispersing agent and 12 parts of composite filler to the stirred tank, and disperse at 1350 rpm for 25 min; S3, adjust the speed to 500 rpm and add 42 parts of styrene-acrylic emulsion to the mixing tank, stir for 12 min, then add 0.3 parts of defoamer and stir for 8 min; S4, system temperature controlled at 32℃, add 2 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 18 min; S5, filtered through a 100-mesh filter, yields the primer; Topcoat preparation: S1, at room temperature, add 28 parts of deionized water to the stirred tank, stir at 400 pm, add 2 parts of dodecyl alcohol ester and 1 part of butanediol isooctyl ether in sequence, stir for 4 min, and adjust the pH of the system to 8.0 using a pH adjuster. S2, add 0.5 parts of ammonium polyacrylate wetting and dispersing agent and 10 parts of modified titanium dioxide to the stirred tank, and disperse at high speed of 1350 rpm for 25 min; S3, adjust the speed to 500 rpm and add 48 parts of pure acrylic emulsion to the mixing tank, stir for 12 min, then add 0.3 parts of defoamer and stir for 8 min; S4, system temperature controlled at 28℃, add 1.8 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 17 min; S5, after being filtered through a 110-mesh filter, yields the topcoat.

[0020] Comparative Example 1 The modification process of modified titanium dioxide is as follows: (a) Solvent dispersion modification: Add aluminate DL-411 to anhydrous ethanol to prepare a 3% (w / w) dilute coupling agent solution, stir evenly to obtain the modified solution; (ii) Powder coating: Add titanium dioxide to the modification liquid, control the solid-liquid ratio at 1:6, and stir at 375 rpm for 45 min; (III) Heating and curing: After stirring, heat to 120℃ and keep warm for 2.5 hours; (iv) Crushing and sieving: After cooling, the agglomerated powder is broken up and passed through a 250-mesh sieve to remove large agglomerated particles. The sieve-under material is collected to obtain modified titanium dioxide. The preparation process of the composite filler is as follows: nano-calcium carbonate (particle size of 50nm) and cenospheres are mixed (the volume ratio of guest filler to cenospheres is 0.35:1; the particle size of cenospheres is 40μm and the shell wall pore size is 450nm), and ultrasonic vibration is performed for 30min to couple the pores and form a composite filler. Primer preparation: S1, at 25℃, add 32 parts of deionized water to the stirred tank, stir at 400 rpm, then add 2 parts of dodecyl alcohol ester and 2 parts of butanediol isooctyl ether in sequence, stir for 4 min, and adjust the pH of the system to 8.0 using a pH adjuster. S2, add 0.5 parts of ammonium polyacrylate wetting and dispersing agent and 12 parts of composite filler to the stirred tank, and disperse at 1350 rpm for 25 min; S3, adjust the speed to 500 rpm and add 42 parts of styrene-acrylic emulsion to the mixing tank, stir for 12 min, then add 0.3 parts of defoamer and stir for 8 min; S4, system temperature controlled at 32℃, add 2 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 18 min; S5, filtered through a 100-mesh filter, yields the primer; Topcoat preparation: S1, at room temperature, add 28 parts of deionized water to the stirred tank, stir at 400 pm, add 2 parts of dodecyl alcohol ester and 1 part of butanediol isooctyl ether in sequence, stir for 4 min, and adjust the pH of the system to 8.0 using a pH adjuster. S2, add 0.5 parts of ammonium polyacrylate wetting and dispersing agent and 10 parts of modified titanium dioxide to the stirred tank, and disperse at high speed of 1350 rpm for 25 min; S3, adjust the speed to 500 rpm and add 48 parts of pure acrylic emulsion to the mixing tank, stir for 12 min, then add 0.3 parts of defoamer and stir for 8 min; S4, system temperature controlled at 28℃, add 1.8 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 17 min; S5, after being filtered through a 110-mesh filter, yields the topcoat.

[0021] Comparative Example 2 The preparation process of the composite filler is as follows: nano-calcium carbonate (particle size of 50nm) and cenospheres are mixed (the volume ratio of guest filler to cenospheres is 0.35:1; the particle size of cenospheres is 40μm and the shell wall pore size is 450nm), and ultrasonic vibration is performed for 30min to couple the pores and form a composite filler. Primer preparation: S1, at 25℃, add 32 parts of deionized water to the stirred tank, stir at 400 rpm, then add 2 parts of dodecyl alcohol ester and 2 parts of butanediol isooctyl ether in sequence, stir for 4 min, and adjust the pH of the system to 8.0 using a pH adjuster. S2, add 0.5 parts of ammonium polyacrylate wetting and dispersing agent and 12 parts of composite filler to the stirred tank, and disperse at 1350 rpm for 25 min; S3, adjust the speed to 500 rpm and add 42 parts of styrene-acrylic emulsion to the mixing tank, stir for 12 min, then add 0.3 parts of defoamer and stir for 8 min; S4, system temperature controlled at 32℃, add 2 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 18 min; S5, filtered through a 100-mesh filter, yields the primer; Topcoat preparation: S1, at room temperature, add 28 parts of deionized water to the stirred tank, stir at 400 pm, add 2 parts of dodecyl alcohol ester and 1 part of butanediol isooctyl ether in sequence, stir for 4 min, and adjust the pH of the system to 8.0 using a pH adjuster. S2, add 0.5 parts of ammonium polyacrylate wetting and dispersing agent and 10 parts of titanium dioxide to the mixing tank, and disperse at high speed of 1350 rpm for 25 min; S3, adjust the speed to 500 rpm and add 48 parts of pure acrylic emulsion to the mixing tank, stir for 12 min, then add 0.3 parts of defoamer and stir for 8 min; S4, system temperature controlled at 28℃, add 1.8 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 17 min; S5, after being filtered through a 110-mesh filter, yields the topcoat.

[0022] Comparative Example 3 The modification process of modified titanium dioxide is as follows: (a) Pretreatment activation: Titanium dioxide was immersed in 0.8 mol / L phosphoric acid solution with a solid-liquid ratio of 1:8 and activated at 90℃ for 3 h. After washing and drying, phosphoric acid activated titanium dioxide was obtained. (ii) Solvent dispersion modification: Add DL-411 aluminate to anhydrous ethanol to prepare a 3% (w / w) dilute coupling agent solution, stir evenly to obtain the modified solution; (III) Powder coating: Add phosphoric acid activated titanium dioxide to the modified liquid, control the solid-liquid ratio at 1:6, and stir at 375 rpm for 45 min; (iv) Heating and curing: After stirring, heat to 120℃ and keep warm for 2.5 hours; (v) Crushing and sieving: After cooling, the agglomerated powder is broken up and passed through a 250-mesh sieve to remove large agglomerated particles. The sieve-under material is collected to obtain modified titanium dioxide. Primer preparation: S1, at 25℃, add 32 parts of deionized water to the stirred tank, stir at 400 rpm, then add 2 parts of dodecyl alcohol ester and 2 parts of butanediol isooctyl ether in sequence, stir for 4 min, and adjust the pH of the system to 8.0 using a pH adjuster. S2, add 0.5 parts of ammonium polyacrylate wetting and dispersing agent and 12 parts of nano calcium carbonate (particle size of 50nm) to the stirred tank, and disperse at 1350rpm for 25min; S3, adjust the speed to 500 rpm and add 42 parts of styrene-acrylic emulsion to the mixing tank, stir for 12 min, then add 0.3 parts of defoamer and stir for 8 min; S4, system temperature controlled at 32℃, add 2 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 18 min; S5, filtered through a 100-mesh filter, yields the primer; Topcoat preparation: S1, at room temperature, add 28 parts of deionized water to the stirred tank, stir at 400 pm, add 2 parts of dodecyl alcohol ester and 1 part of butanediol isooctyl ether in sequence, stir for 4 min, and adjust the pH of the system to 8.0 using a pH adjuster. S2, add 0.5 parts of ammonium polyacrylate wetting and dispersing agent and 10 parts of modified titanium dioxide to the stirred tank, and disperse at high speed of 1350 rpm for 25 min; S3, adjust the speed to 500 rpm and add 48 parts of pure acrylic emulsion to the mixing tank, stir for 12 min, then add 0.3 parts of defoamer and stir for 8 min; S4, system temperature controlled at 28℃, add 1.8 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 17 min; S5, after being filtered through a 110-mesh filter, yields the topcoat.

[0023] Comparative Example 4 The modification process of modified titanium dioxide is as follows: (a) Pretreatment activation: Titanium dioxide was immersed in 0.8 mol / L phosphoric acid solution with a solid-liquid ratio of 1:8 and activated at 90℃ for 3 h. After washing and drying, phosphoric acid activated titanium dioxide was obtained. (ii) Solvent dispersion modification: Add DL-411 aluminate to anhydrous ethanol to prepare a 3% (w / w) dilute coupling agent solution, stir evenly to obtain the modified solution; (III) Powder coating: Add phosphoric acid activated titanium dioxide to the modified liquid, control the solid-liquid ratio at 1:6, and stir at 375 rpm for 45 min; (iv) Heating and curing: After stirring, heat to 120℃ and keep warm for 2.5 hours; (v) Crushing and sieving: After cooling, the agglomerated powder is broken up and passed through a 250-mesh sieve to remove large agglomerated particles. The sieve-under material is collected to obtain modified titanium dioxide. Primer preparation: S1, at 25℃, add 32 parts of deionized water to the stirred tank, stir at 400 rpm, then add 2 parts of dodecyl alcohol ester and 2 parts of butanediol isooctyl ether in sequence, stir for 4 min, and adjust the pH of the system to 8.0 using a pH adjuster. S2, add 0.5 parts of ammonium polyacrylate wetting and dispersing agent and 12 parts of cenospheres (the particle size of the cenospheres is 40 μm and the shell wall pore size is 450 nm) to the stirred tank, and disperse at 1350 rpm for 25 min; S3, adjust the speed to 500 rpm and add 42 parts of styrene-acrylic emulsion to the mixing tank, stir for 12 min, then add 0.3 parts of defoamer and stir for 8 min; S4, system temperature controlled at 32℃, add 2 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 18 min; S5, filtered through a 100-mesh filter, yields the primer; Topcoat preparation: S1, at room temperature, add 28 parts of deionized water to the stirred tank, stir at 400 pm, add 2 parts of dodecyl alcohol ester and 1 part of butanediol isooctyl ether in sequence, stir for 4 min, and adjust the pH of the system to 8.0 using a pH adjuster. S2, add 0.5 parts of ammonium polyacrylate wetting and dispersing agent and 10 parts of modified titanium dioxide to the stirred tank, and disperse at high speed of 1350 rpm for 25 min; S3, adjust the speed to 500 rpm and add 48 parts of pure acrylic emulsion to the mixing tank, stir for 12 min, then add 0.3 parts of defoamer and stir for 8 min; S4, system temperature controlled at 28℃, add 1.8 parts of polycarbodiimide crosslinking agent to the stirred tank and stir for 17 min; S5, after being filtered through a 110-mesh filter, yields the topcoat.

[0024] Performance testing Sample preparation: Bamboo fiberboard is used as the substrate; a primer is sprayed first, and then a topcoat is sprayed after it dries. Total dry film thickness of composite coating: 50μm (20μm primer + 30μm topcoat); Standard curing conditions for the paint film: complete curing at 23℃ and 50%RH for 7 days.

[0025] (I) Water resistance performance of Examples 1-4 and Comparative Examples 1-4 was tested according to the method in GB / T1733-2020 "Determination of Water Resistance of Paints and Varnishes - Immersion Method"; Test conditions: distilled water at 23±2℃; Water resistance value represents the immersion time for the first appearance of blistering, peeling, or permanent whitening defects in the paint film; Test results are shown in Table 1: Table 1

[0026] As can be seen from Table 1, the water resistance of the paint films in Examples 1-4 can reach 90-98h; while the water resistance of the paint films in Comparative Examples 1-4 is only 68-75h. Compared to the comparative example, the coating of the present invention has a significantly longer water resistance time, delays the penetration of water into the paint film, maintains the integrity of the paint film for a longer period of time, and is free from defects such as blistering, peeling, and permanent whitening. Its waterproof barrier performance is significantly better than that of the comparative example.

[0027] (II) Performance tests were conducted on Examples 1-4 and Comparative Examples 1-4 according to the methods in GB / T1865-2009 "Artificial Climate Aging and Artificial Radiation Exposure to Filtered Xenon Arc Radiation for Paints and Varnishes". Test conditions: The samples were placed in the testing equipment, and the spectral irradiance at a wavelength of 340 nm using a sunlight filter was 0.51 W / ( The equipment's internal air temperature was 40℃ and relative humidity was 50%; the circulation mode consisted of 102 minutes of light exposure followed by 18 minutes of deionized water spraying; the total exposure time was 800 hours. The test results are shown in Table 2. Table 2

[0028] As can be seen from Table 2, the gloss loss rate of the coatings in Examples 1-4 was 12-15%, the area of ​​coating peeling off after aging was 3-5%, and the pencil hardness decreased from H to HB, with only a decrease of 1 grade; the gloss loss rate of the coatings in Comparative Examples 1-4 reached 20-25%, and the area of ​​peeling off after aging was 11-18%. Among them, the pencil hardness of Comparative Examples 3 and 4 decreased from H to B, with a greater decrease in hardness. Compared to the comparative example, the coating of the present invention exhibits lower gloss loss, better adhesion retention, less hardness decay, and significantly better resistance to artificial weathering than the comparative example.

[0029] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.

Claims

1. A waterproof paint for wall panels, characterized in that, The waterproof paint for the wall panel is obtained by spraying a primer and a topcoat in layers. The primer is composed of the following raw materials in parts by weight: 38-48 parts styrene-acrylic emulsion, 1.2-2.5 parts polycarbodiimide crosslinking agent, 1.8-2.8 parts dodecyl alcohol ester, 1-2 parts butanediol isooctyl ether, 0.3-0.8 parts ammonium polyacrylate wetting and dispersing agent, 0.2-0.5 parts defoamer, 9-16 parts composite filler, and 26-36 parts deionized water; The topcoat is composed of the following raw materials in parts by weight: 42-52 parts pure acrylic emulsion, 1.2-2.5 parts polycarbodiimide crosslinking agent, 2-3 parts dodecyl alcohol ester, 1-2 parts butylene glycol isooctyl ether, 0.3-0.8 parts ammonium polyacrylate wetting and dispersing agent, 0.2-0.4 parts defoamer, 7-13 parts modified titanium dioxide, and 24-34 parts deionized water.

2. The waterproof paint for wall panels according to claim 1, characterized in that, The modification process of the modified titanium dioxide is as follows: (a) Pretreatment activation: Titanium dioxide is immersed in 0.5-1.0 mol / L phosphoric acid solution with a solid-liquid ratio of 1:5-1:10 and activated at 80-100℃ for 2-4 hours. After washing and drying, phosphoric acid activated titanium dioxide is obtained. (ii) Solvent dispersion modification: Add DL-411 aluminate to anhydrous ethanol to prepare a 2-5% mass fraction coupling agent dilute solution, stir evenly to obtain the modified solution; (III) Powder coating: Add phosphoric acid activated titanium dioxide to the modified liquid, control the solid-liquid ratio at 1:4-1:8, and stir at 350-400 rpm for 30-60 min; (iv) Heating and curing: After stirring, heat to 110-130℃ and keep warm for 1.5-3 hours; (v) Crushing and sieving: After cooling, the agglomerated powder is broken up and passed through a 200-300 mesh sieve to remove large agglomerated particles. The sieve material is collected to obtain modified titanium dioxide.

3. The waterproof paint for wall panels according to claim 1, characterized in that, The composite packing is composed of a guest packing and a host material coupled through pores; the volume ratio of the guest packing to the host material is 0.35:

1.

4. The waterproof paint for wall panels according to claim 3, characterized in that, The preparation process of the composite filler is as follows: the guest filler and the host material are mixed and ultrasonically vibrated for 20-40 minutes to couple the pores and form a composite filler.

5. The waterproof paint for wall panels according to claim 4, characterized in that, The guest filler is selected from one or more of nano-calcium carbonate and nano-rutile, wherein the nano-calcium carbonate has a particle size of 40-60 nm, and the nano-rutile... The particle size is 25-40 nm.

6. The waterproof paint for wall panels according to claim 5, characterized in that, The host material is selected as cenospheres; the particle size of the cenospheres is 30-50μm, and the shell wall pores are 200nm-600nm.

7. A method for preparing the waterproof paint for wall panels according to any one of claims 1-6, characterized in that, Includes the following steps: Primer preparation: S1, at 25℃, add deionized water to the stirred tank and stir at 300-500 rpm. Then add dodecyl alcohol ester and butanediol isooctyl ether in sequence and stir for 3-5 min. Adjust the pH of the system to 7.5-9.0 using a pH adjuster. S2, add ammonium polyacrylate wetting and dispersing agent and composite filler to the stirred tank, and disperse at 1200-1500 rpm for 20-30 min; S3, adjust the speed to 400-600 rpm and add styrene-acrylic emulsion to the mixing tank, stir for 10-15 minutes, then add defoamer and stir for 5-10 minutes; S4, system temperature controlled at 30-35℃, add polycarbodiimide crosslinking agent to the stirred tank and stir for 15-20 minutes; S5, filtered through an 80-120 mesh filter, yields the primer; Topcoat preparation: S1, at room temperature, add deionized water to the stirred tank and stir at 300-500 rpm. Then add dodecyl alcohol ester and butanediol isooctyl ether in sequence and stir for 3-5 minutes. Adjust the pH of the system to 7.5-9.0 using a pH adjuster. S2, add ammonium polyacrylate wetting and dispersing agent and modified titanium dioxide into the stirred tank, and disperse at high speed of 1200-1500 rpm for 20-30 min; S3, adjust the speed to 400-600 rpm and add pure acrylic emulsion to the mixing tank, stir for 10-15 minutes, then add defoamer and stir for 5-10 minutes; S4, system temperature controlled at 25-30℃, add polycarbodiimide crosslinking agent to the stirred tank and stir for 15-20 min; S5, after being filtered through a 100-120 mesh filter, yields the topcoat.